2014
DOI: 10.1310/hct1505-185
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the 2013 WHO Antiretroviral Therapy Guidelines on the Feasibility of HIV Population Prevention Trials

Abstract: Introduction Several cluster-randomized HIV prevention trials aim to demonstrate the population-level preventive impact of antiretroviral therapy (ART). 2013 World Health Organization guidelines raising the ART initiation threshold to CD4<500/µL could attenuate these trials’ effect size by increasing ART usage in control clusters. Methods We used a computational model to simulate strategies from a hypothetical cluster-randomized HIV prevention trial. The primary model outcome was the relative reduction in 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“… 6 This was further supported by Ross et al who found that SSA countries had some national explicit policies that targeted increasing ART access in line with the WHO 2013 guidelines on ART. 19 In his study, Hsieh et al indicated that community consultations are crucial if policies are to be effectively implemented. 6 Labhardt et al found that health centres in Lesotho took longer to adopt the new guidelines because of limited knowledge of WHO policy changes.…”
Section: Resultsmentioning
confidence: 99%
“… 6 This was further supported by Ross et al who found that SSA countries had some national explicit policies that targeted increasing ART access in line with the WHO 2013 guidelines on ART. 19 In his study, Hsieh et al indicated that community consultations are crucial if policies are to be effectively implemented. 6 Labhardt et al found that health centres in Lesotho took longer to adopt the new guidelines because of limited knowledge of WHO policy changes.…”
Section: Resultsmentioning
confidence: 99%
“…[1]. The de nition of INR is that the virus replication is controlled by cART for 1 year, but the CD4 + T cell count is still less than 200/ul by at least two years after the treatment [2]. On the other hand, the immune responder (IR) is de ned when CD4 + T cell count is greater than 200/ul after the treatment.…”
Section: Introductionmentioning
confidence: 99%